Xenon-Enhanced Dynamic Dual-Energy CT Is Able to Quantify Sinus Ventilation Using Laminar and Pulsating Air-/Gas Flow Before and After Surgery: A Pilot Study in a Cadaver Model - Becker, Sven; Huppertz, Tilman; Möller, Winfried; Havel, Miriam; Schuster, Maria; Becker, Anne Merle; Sailer, Martin; Schuschnig, Uwe; Johnson, Thorsten R. (Frontiers in Allergy, 2022)
Background Chronic rhinosinusitis is a common disease with a significant impact on the quality of life. Topical drug delivery to the paranasal sinuses is not efficient to prevent sinus surgery or expensive biologic treatment in a lot of cases as the affected mucosa is not reached. More efficient approaches for topical drug delivery are, therefore, necessary. In the current study, dual-energy CT (DECT) imaging was used to examine sinus ventilation before and after sinus surgery using a pulsating xenon gas ventilator in a cadaver head. Methods Xenon gas was administered to the nasal cavity of a cadaver head with a laminar flow of 7 L/min and with pulsating xenon-flow (45 Hz frequency, 25 mbar amplitude). Nasal cavity and paranasal sinuses were imaged by DECT. This procedure was repeated after functional endoscopic sinus surgery (FESS). Based on the enhancement levels in the different sinuses, regional xenon concentrations were calculated. Results Xenon-related enhancement could not be detected in most of the sinuses during laminar gas flow. By superimposing laminar flow with pulsation, DECT imaging revealed a xenon wash-in and wash-out in the sinuses. After FESS, xenon enhancement was immediately seen in all sinuses and reached higher concentrations than before surgery. Conclusion Xenon-enhanced DECT can be used to visualize and quantify sinus ventilation. Pulsating air-/gas flow was superior to laminar flow for the administration of xenon to the paranasal sinuses. FESS leads to successful ventilation of all paranasal sinuses.